Primer Sledilnik - Kostanjevec, Jan (Javnost (Ljubljana), 2021)
Among other things, the Covid-19 pandemic uncovered important ruptures in the Slovenian data infrastructure. As a response, a community named Sledilnik /Tracker/ was established. It started with community-driven decontextualisation and centralisation of Slovenian pandemic data for its own needs. Soon, it started to off er public data and expert services for an ever wider and more diverse group of users, thus becoming an important part of the Slovenian pandemic-related data infrastructure. This article explores the development of this community, the role of boundary objects and organisational principles within it as well as the activities they supported. Besides establishing a data infrastructure, these include various expert services and advocating activities for ”data excellence” and open data. The results hint at the limits of peer production in the area of data curation stemming from low modularity and granularity of this kind of work. Results also point to the fact that the theory of boundary objects as well as some theories of public spheres presuppose a minimal cooperativeness of important social actors, which is not necessarily a given in such circumstances.
Keywords: Covid-19; Epidemics; Epidemije; obdelava podatkov; odprta koda; pandemije; podatkovne zbirke; Prostovoljno delo; Sledilnik; Statistical data; Statistični podatki; Volunteer work